Saúde coletica e COVID-19: o aporte da comunidade científica brasileira no enfrentamento da pandemia. - MATEUS, Isabella Maria Almeida (Universidade Federal do Pará, 2024)
The rapid spread of COVID-19 around the world has caused the number of research related to the disease to also increase at a rapid pace, setting up an unprecedented scientific race. The Brazilian Collective Health scientific community was also involved in this movement. To visualize Brazil's contribution in this field, this work seeks to analyze the profile and contribution of the Brazilian Collective Health scientific production in the face of the COVID-19 pandemic. This is a bibliographic study, which used domain analysis as a method and applied bibliometric and altmetric instruments, as well as content analysis. Scientific production was measured using indicators of productivity, impact, and visibility. For these purposes, articles on Collective Health and COVID-19 were searched in the Web of Science, Scopus, SciELO, and PubMed Central databases, with Brazil as the country of affiliation of one or more authors, and the publication period delimited from Jan./2020 to Dec./2021. As a result, 735 articles were selected and received 7,027 citations. The Southeast Region showed the highest number of publications (51.56%), and the University of São Paulo was the most productive institution (6.88% of articles). The area managed to articulate with researchers from 827 institutions in 71 countries. The most productive author published 18 papers. Only 25.44% of the articles mentioned a source of funding. The 100 most cited articles had 47,982 interactions on social media platforms, the majority from Twitter (54.76%) by members of the general public (92.69%). The article with the highest rate of attention on social media ranked 82nd in the most cited ranking. A total of 14 subjects were identified. “Health care in the pandemic” showed the majority of articles. However, “Epidemiology and health surveillance in the pandemic context” was the most relevant topic for the scientific community and the one that aroused greater interest in the general public. We concluded that the articles analyzed in this study reflect the Brazilian scientific production and were considered relevant, as they were cited by other authors in their studies and also attracted the attention of the lay public. Two waves of scientific production were observed, possibly following the pace of activity of Brazilian universities and institutes. Due to the low number of articles generated by the North Region, the formation of an academic staff of Collective Health in this region was seen as necessary. An article was used as an example to demonstrate that a high number of citations or mentions in social networks does not always correspond to quality. Although science is not completely impartial and depoliticized, it has mechanisms of self-criticism and self-refutation, thus showing its value. The interaction between what science produces and what is disseminated on social networks needs more attention and better regulations in order to avoid that the information generated in this area ends up being distorted. Finally, new studies are proposed to understand why some subjects attract greater interest from the lay public, but not so much from the scientific community.